Clostridial toxins in neonatal necrotising enterocolitis. Issue 3 (March 1984) - Thomas, D F; Fernie, D S; Bayston, R; Spitz, L
Abstract : Clostridium difficile cytopathic toxin was found in the faeces or gut content of five of 39 neonates with necrotising enterocolitis (NEC). Toxin concentrations were uniformly low and did not differ from those found in healthy neonates. C difficile is unlikely to be involved in the pathogenesis of NEC. Stools from 33 babies with NEC were also tested for C perfringens alpha toxin, with negative results.